2018
DOI: 10.1007/s12275-018-7548-y
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiota and the immune system in metabolic diseases

Abstract: The intestinal microbiota is comprised of millions of microorganisms that reside in the gastrointestinal tract and consistently interact with the host. Host factors such as diet and disease status affect the composition of the microbiota, while the microbiota itself produces metabolites that can further manipulate host physiology. Dysbiosis of the intestinal microbiota has been characterized in patients with certain metabolic diseases, some of which involve damage to the host intestinal epithelial barrier and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 81 publications
1
66
0
1
Order By: Relevance
“…Intestinal microbiota is recently referred as a "hidden organ," including a wide range of bacteria, with an extension of a gene pool much more abundant than that from the host. Intestinal microbiota and perturbations in the composition of the microbiota support numerous nutritional, metabolic, immunological, and physiological processes [8][9][10][11]. Amit-Romach et al [12] found that VAD diets alter the composition of intestinal microflora by decreasing the relative proportion of lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal microbiota is recently referred as a "hidden organ," including a wide range of bacteria, with an extension of a gene pool much more abundant than that from the host. Intestinal microbiota and perturbations in the composition of the microbiota support numerous nutritional, metabolic, immunological, and physiological processes [8][9][10][11]. Amit-Romach et al [12] found that VAD diets alter the composition of intestinal microflora by decreasing the relative proportion of lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study indicated that DAP induced the metabolism of the colon microflora by increasing the production of six types of short‐chain fatty acids (Liu et al ., ), which results were in line with those from this study. An increasing number of studies have shown that the colon microbiota has great benefits in immune homeostasis and autoimmunity; and play an important role in the development of CD4 + cells both within and outside the intestine (Ekmekciu et al ., ; Sittipo et al ., ). The Erysipelotrichaceae genus, which appeared to be highly immunogenic and could potentially flourish post‐treatment with broad spectrum antibiotics, was significantly increased in abundance ( P value < 0.05), inferring with the potential of DAP to promote colon immunity via this specific pathway (Kaakoush, ).…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, as this is not a placebo-controlled trial, the effects could be due to other environmental changes. Finally, there is also the possibility that albendazole affects macro- and microbiomes directly, which can affect the immune system [33-35]. …”
Section: Discussionmentioning
confidence: 99%